Excess smoking in malignant-phase hypertension. Issue 6163 (3rd March 1979) - Isles, C; Brown, J J; Cumming, A M M; Lever, A F; McAreavey, D; Robertson, J I S; Hawthorne, V M; Stewart, G M; Robertson, J W K; Wapshaw, J
Abstract : The smoking habits of 82 patients with malignant-phase hypertension were compared with those of subjects in three control groups matched for age and sex. Sixty-seven (82%) of the patients with malignant-phase hypertension were smokers compared with 41 (50%) and 71 (43%) of the patients in two control groups with non-malignant hypertension, and 43 people (52%) in a general population survey. The excess of smokers in the malignant-phase group was significant for men and women, together and separately, for cigarette smoking alone, and for all forms of smoking. There were no significant differences between the control groups. The chance of a hypertensive patient who smoked having the malignant phase was five times that of a hypertensive patient who did not. Twelve patients in the malignant-phase group had never smoked. All were alive three and a half years on average after presentation (range 11 months to seven years). Twenty-four (36%) of the smokers with malignant-phase hypertension died during the same period. The mortality rate was significantly higher among patients with renal failure, as was the prevalence of smoking. Eighteen patients with malignant-phase hypertension had a serum creatinine concentration higher than 250 μmol/l (2·8 mg/100 ml); 17 were smokers and one an ex-smoker. Eleven of these 18 patients died. It is concluded that hypertensive patients who smoke are much more likely to develop the malignant phase than those who do not, and that once the condition has developed it follows a particularly lethal course in smokers.